Integrating Educational Technology to Increase Teacher Creativity Through Servant Leadership - Supriatman, Eman; Setyaningsih, Sri; Suhendra, Suhendra (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aims to analyze the effect of educational technology integration on improving teacher creativity through the application of servant leadership. The focus is to understand how servant leadership can create an environment that supports teachers' use of technology and enhances their creativity in teaching. Methods: A quantitative approach was used with a survey method. Data were collected through questionnaires distributed to 200 teachers in Indonesian schools. The variables studied included the application of servant leadership, the use of technology in learning, and teacher creativity. Data were analyzed using regression to measure the relationship between variables. Results: The results show that servant leadership has a positive and significant effect on the use of technology in learning, which in turn enhances teacher creativity. Leaders who provide active support and adequate resources create an environment that supports technology-based learning innovation, which positively impacts teaching quality. Novelty: This study contributes new insights by combining servant leadership and educational technology as mutually supportive factors in enhancing teacher creativity. The findings enrich the literature on educational leadership and provide practical insights for school principals to enhance teacher creativity through technology.